2012
DOI: 10.1007/s00405-012-2114-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of botulinum toxin injections into the cricopharyngeus muscle of patients with cricopharyngeus dysfunction associated with pharyngo-laryngeal weakness

Abstract: This prospective, open study was carried out in order to assess changes in the swallowing and dietary status after injection of Botulinum toxin A (BoNT-A) into the upper esophageal sphincter (UES) in a series of patients with cricopharyngeus (CP) muscle dysfunction associated with pharyngo-laryngeal weakness during at least 1 year follow-up after treatment. Patients who had a cricopharyngeus (CP) muscle dysfunction associated with pharyngo-laryngeal weakness and who were at risk for aspiration were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…27 Although Terre et al recommended BoT injections for patients who had incomplete relaxation of the CP muscle with a certain degree of pharyngeal propulsion, Woisard-Bassols et al reported good outcomes in patients with CP dysfunction and pharyngolaryngeal weakness. 29 Our review found that BoT injections are not as successful as myotomy, and as the invasiveness of the procedure increased (BoT 5 low, dilatation 5 medium, myotomy 5 high), there was a statistically significant trend favoring increased success rates.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…27 Although Terre et al recommended BoT injections for patients who had incomplete relaxation of the CP muscle with a certain degree of pharyngeal propulsion, Woisard-Bassols et al reported good outcomes in patients with CP dysfunction and pharyngolaryngeal weakness. 29 Our review found that BoT injections are not as successful as myotomy, and as the invasiveness of the procedure increased (BoT 5 low, dilatation 5 medium, myotomy 5 high), there was a statistically significant trend favoring increased success rates.…”
Section: Discussionmentioning
confidence: 78%
“…1). Twelve studies 4,8,22,[24][25][26][27][28][29][30][31][32] were prospective and 20 2,5,6,9,10,14,18,21,[33][34][35][36][37][38][39][40][41][42][43][44] were retrospective. All of the publications were observational studies, with a level of evidence of IV; with the exception of one prospective cohort study (IIb) ( Table II).…”
Section: Resultsmentioning
confidence: 99%
“…This may explain the lack of effect of BTX treatment in some patients and maybe also the side effects. Electromyography guidance for BTX injection has been shown useful in pharyngeal dysfunction, but this cannot be applied to LES or esophageal body muscular layer . Endoscopic ultrasound (EUS) guidance has been proposed for esophageal BTX injection into the LES to treat achalasia, with good results .…”
Section: Discussionmentioning
confidence: 99%
“…However, drug therapies are often limited because of side effects or lack of efficacy . Surgical or more recently endoscopic esophageal myotomy has been proposed for the most severe cases …”
Section: Introductionmentioning
confidence: 99%
“…Myotomy of CM is the treatment of choice for the hyperactivity of the UES due to neurologic disorders [5], but it is generally suggested when other interventions have failed. BoNT-A has been widely reported as efficacious therapeutic medical tool for the treatment of dysphagia due to the spasticity of CM [6][7][8]. However, when using BoNT-A for the treatment of dysphagia, the doses that are commonly injected could result ineffective.…”
Section: Introductionmentioning
confidence: 99%